Carbon-coated titanium-niobium oxide, preparation method and application thereof
Patent Information
- Application Number
- CN202611301075.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-27
AI Technical Summary
本申请通过在TiNb2O7基体材料的外周设置碳包覆层,碳包覆层中包括无定形碳粘接相与导电组分,由此在TiNb2O7基体材料表面形成连续接触的层状电荷转移界面。进一步地,无定形碳粘接相与TiNb2O7基体材料表面紧密贴合,有利于使电子从导电组分传输至每一个TiNb2O7基体材料内部,从而降低界面接触电阻。值得一提的是,第一导电填料以线状连接若干一次颗粒中的TiNb2O7基体材料以形成导电路径,从而跨越一次颗粒之间的物理间隙,在TiNb2O7基体材料之间搭建局域桥接通道。这种线状的导电路径绕开TiNb2O7基体材料之间因物理接触而产生的界面接触电阻,使电子可沿第一导电填料快速穿过TiNb2O7基体材料之间的间隙,避免电子在TiNb2O7基体材料间点接触的界面处产生累积与损耗。在此基础上,第二导电填料在无定形碳粘接相中形成网状的贯穿于碳包覆层的导电骨架,有利于形成电子高速传输导电网络。
Smart Images

Figure CN122992039A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of electrode materials technology, and in particular to a carbon-coated titanium niobium oxide, its preparation method and application. Background Technology
[0002] Lithium-ion batteries, as a key carrier of new energy storage technology, are widely used in new energy vehicles, consumer electronics, and large-scale energy storage. With the market's increasing demands for lithium-ion battery performance, especially the increasingly stringent requirements for driving range and safety, lithium-ion battery technology continues to iterate and upgrade towards higher energy density and higher safety.
[0003] Titanium niobium oxide (TiNb₂O₇) possesses advantages such as stable operating voltage (1.0V–2.5V), high structural stability, excellent safety, and no risk of lithium dendrite formation, making it a promising candidate material for next-generation high-power, ultra-fast-charging lithium-ion battery anodes. It shows broad application prospects in power batteries, energy storage systems, power tools, and drones. However, TiNb₂O₇ has extremely low intrinsic electronic conductivity (typically below 10). -9 S / cm~10 -12 (On the order of S / cm), lithium-ion diffusion rate is slow (approximately 10). - 14 cm 2 / s~10 -13 cm 2 The electron conduction bottleneck (electrons per second) makes electron transport within the material and between particles extremely difficult. Furthermore, TiNb2O7 exhibits severe polarization under ultra-fast charging conditions above 50C, resulting in a sharp capacity decay that fails to meet the demands of high-power applications. This electronic conduction bottleneck leads to severe polarization during charging and discharging, particularly at high rates, hindering the effective utilization of its capacity and severely restricting its commercial application. Summary of the Invention
[0004] One objective of this application is to provide a carbon-coated titanium niobium oxide, its preparation method and application, which is beneficial for obtaining carbon-coated titanium niobium oxide with good electron transport performance, good stability in use and service life.
[0005] To achieve the above objectives, this application provides a carbon-coated titanium niobium oxide, which is assembled from a plurality of primary particles. Each primary particle comprises: a TiNb2O7 matrix material; and a carbon coating layer, which coats the TiNb2O7 matrix material. The carbon coating layer includes an amorphous carbon binder phase and a conductive component. At least a portion of the amorphous carbon binder phase connects the TiNb2O7 matrix material and the conductive component, and the conductive component is dispersed within the amorphous carbon binder phase. The conductive component includes a first conductive filler and a second conductive filler. At least a portion of the first conductive filler connects at least two of the TiNb2O7 matrix materials in the primary particles to form a conductive path. At least a portion of the second conductive filler forms a conductive framework penetrating the carbon coating layer within the amorphous carbon binder phase of the plurality of primary particles.
[0006] In some embodiments, the first conductive filler is selected from at least one of single-walled carbon nanotubes and double-walled carbon nanotubes, and the second conductive filler is multi-walled carbon nanotubes; the amorphous carbon binder phase is obtained by carbonization of a carbon precursor, wherein the carbon precursor is selected from water-soluble sugars, water-soluble organic acids, or water-soluble polymers.
[0007] In some embodiments, at least one of the following conditions is met: (a) the ratio of the diameter of the TiNb2O7 matrix material to the thickness of one side of the carbon coating layer is (5~80):1; (b) the median particle size D50 of the TiNb2O7 matrix material is 0.08μm~0.15μm; (c) the mass ratio of the TiNb2O7 matrix material, the carbon precursor, the first conductive filler, and the second conductive filler is (80~120):(2~12):(0.1~0.6):(0.5~3); (d) the mass of the TiNb2O7 matrix material is m1, the sum of the masses of the carbon precursor, the first conductive filler, and the second conductive filler is m2, and 0.05m1≤m2≤0.16m1; (e) the median particle size D50 of the carbon-coated titanium niobium oxide is 0.5μm~5μm.
[0008] To achieve the above objectives, this application also provides a method for preparing carbon-coated titanium niobium oxide, comprising the following steps: S100, providing a titanium source and a niobium source, and calcining them to obtain a TiNb2O7 matrix material; S200, wet grinding the TiNb2O7 matrix material, a carbon precursor, and a conductive component to obtain a mixed slurry, and drying the mixed slurry to obtain an intermediate powder, wherein the conductive component includes a first conductive filler and a second conductive filler; S300, calcining the intermediate powder in a protective gas to coat the outer periphery of the TiNb2O7 matrix material with a carbon coating layer, wherein the carbon coating layer includes an amorphous carbon binder phase and the conductive component, wherein the carbon precursor is converted into the amorphous carbon binder phase, at least a portion of the first conductive filler connects at least two of the TiNb2O7 matrix materials to form a conductive path, and at least a portion of the second conductive filler forms a conductive skeleton penetrating the carbon coating layer in the amorphous carbon binder phase, thereby obtaining carbon-coated titanium niobium oxide.
[0009] In some embodiments, the titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, titanium isopropoxide, and titanium sulfate, and the niobium source is selected from at least one of niobium pentoxide, niobium pentachloride, niobium ethanol, niobium oxalate, and ammonium niobium oxalate; the number of moles of titanium in the titanium source is n1, the number of moles of niobium in the niobium source is n2, and the ratio between n1 and n2 is (0.8~1.2):(1.5~2.5).
[0010] In some embodiments, the mass ratio of the TiNb2O7 matrix material, the carbon precursor, the first conductive filler, and the second conductive filler is (80~120):(2~12):(0.1~0.6):(0.5~3).
[0011] In some embodiments, in step S100, the calcination temperature is 800℃~1200℃, the calcination time is 2h~6h, and the calcination heating rate is 2℃ / min~5℃ / min; in step S300, the calcination temperature is 600℃~800℃, the calcination time is 2h~6h, and the calcination heating rate is 2℃ / min~5℃ / min.
[0012] In some embodiments, the median particle size D50 of the TiNb2O7 matrix material is 0.08 μm to 0.15 μm, the single-sided thickness of the carbon coating layer is 2 nm to 5 nm, and the median particle size D50 of the carbon-coated titanium niobium oxide is 0.5 μm to 5 μm.
[0013] To achieve the above objectives, this application also provides an electrode sheet comprising carbon-coated titanium niobium oxide as described above or carbon-coated titanium niobium oxide prepared by the aforementioned preparation method.
[0014] To achieve the above objectives, this application also provides a battery including at least one electrode as described above.
[0015] Compared with the prior art, the beneficial effects of this application are as follows: This application creates a continuous, layered charge transfer interface on the surface of the TiNb2O7 matrix material by forming a carbon coating layer on the outer periphery of the matrix material. This carbon coating layer includes an amorphous carbon binder phase and a conductive component. Furthermore, the amorphous carbon binder phase adheres tightly to the surface of the TiNb2O7 matrix material, facilitating electron transfer from the conductive component to the interior of each TiNb2O7 matrix material, thereby reducing interfacial contact resistance. Notably, a first conductive filler connects several primary TiNb2O7 matrix materials in a linear fashion to form a conductive path, bridging the physical gaps between primary particles and establishing localized bridging channels between the TiNb2O7 matrix materials. This linear conductive path bypasses the interfacial contact resistance caused by physical contact between the TiNb2O7 matrix materials, allowing electrons to quickly pass through the gaps between the TiNb2O7 matrix materials along the first conductive filler, preventing electron accumulation and loss at the point contact interfaces between the TiNb2O7 matrix materials. Based on this, the second conductive filler forms a network-like conductive framework that penetrates the carbon coating layer in the amorphous carbon binder phase, which is conducive to the formation of a high-speed electron transport conductive network.
[0016] Furthermore, in this application, the carbon-coated titanium niobium oxide is assembled from several primary particles. A first conductive filler provides linear local bridging between the primary particles, while a second conductive filler provides a network-like interconnection between them. This creates a three-tiered electronic conduction pathway within the secondary aggregates assembled from the primary particles, from the "TiNb2O7 matrix material surface (layer)" to the "linear local bridging" and then to the "network-like conductive framework penetrating the carbon coating layer." In other words, the amorphous carbon binder phase provides a tight interface with the TiNb2O7 matrix material surface, which is beneficial for improving the interfacial efficiency of charge transfer. The first conductive filler enhances the local electron transport performance between primary particles. The second conductive filler ensures long-range rapid electron transport at the macroscopic electrode scale. Attached Figure Description
[0017] Figure 1 These are scanning electron microscope images of carbon-coated titanium niobium oxide obtained in Example 1 of this application, wherein (a), (b), (c), and (d) are scanning electron microscope images at different magnifications.
[0018] Figure 2 The X-ray diffraction patterns are those of Example 1 and Comparative Example 10 of this application. Detailed Implementation
[0019] The present application will be further described below with reference to specific embodiments. It should be noted that, without conflict, the various embodiments or technical features described below can be arbitrarily combined to form new embodiments.
[0020] As used herein, the terms “prepared from” and “comprising” are synonymous. The terms “comprising,” “including,” “having,” “containing,” or any other variation thereof, as used herein, are intended to cover non-exclusive inclusion. For example, a composition, step, method, article, or apparatus that includes the listed elements is not necessarily limited to those elements and may include other elements not expressly listed or elements inherent to such composition, step, method, article, or apparatus.
[0021] When a quantity, concentration, or parameter is expressed as a range, a preferred range, or a range defined by a series of upper and lower preferred values, this should be understood as specifically disclosing any pair of any upper or preferred value with any lower or preferred value, regardless of whether the range is disclosed individually. For example, when the range is disclosed as “1 to 5”, the described range should be interpreted as including ranges “1 to 4”, “1 to 3”, “1 to 2 and 4 to 5”, “1 to 3 and 5”, etc. When numerical ranges are described herein, unless otherwise stated, the range includes its endpoints and all integers and fractions within that range.
[0022] Approximate terms used in the specification and claims to modify quantities indicate that the invention is not limited to that specific quantity, but also includes acceptable modifications close to that quantity that do not alter the relevant essential function. Correspondingly, the use of "about," "approximately," etc., to modify a numerical value means that the invention is not limited to that precise value. In some instances, approximate terms may correspond to the precision of the instrument used to measure the value. In this application's specification and claims, scope definitions can be combined and / or interchanged, unless otherwise stated, these scopes include all subscopes contained therein.
[0023] This application provides a carbon-coated titanium niobium oxide, which is assembled from a plurality of primary particles. The primary particles include: a TiNb2O7 matrix material; a carbon coating layer, which coats the outer periphery of the TiNb2O7 matrix material. The carbon coating layer includes an amorphous carbon binder phase and a conductive component. At least a portion of the amorphous carbon binder phase connects the TiNb2O7 matrix material and the conductive component. The conductive component is dispersed in the amorphous carbon binder phase. The conductive component includes a first conductive filler and a second conductive filler. At least a portion of the first conductive filler connects at least two TiNb2O7 matrix materials in the primary particles to form a conductive path. At least a portion of the second conductive filler overlaps with each other in the amorphous carbon binder phase of the plurality of primary particles to form a conductive framework that penetrates the carbon coating layer.
[0024] This application creates a continuous, layered charge transfer interface on the surface of the TiNb2O7 matrix material by forming a carbon coating layer on the outer periphery of the matrix material. This carbon coating layer includes an amorphous carbon binder phase and a conductive component. Furthermore, the amorphous carbon binder phase adheres tightly to the surface of the TiNb2O7 matrix material, facilitating electron transfer from the conductive component to the interior of each TiNb2O7 matrix material, thereby reducing interfacial contact resistance. Notably, a first conductive filler connects several primary TiNb2O7 matrix materials in a linear fashion to form a conductive path, bridging the physical gaps between primary particles and establishing localized bridging channels between the TiNb2O7 matrix materials. This linear conductive path bypasses the interfacial contact resistance caused by physical contact between the TiNb2O7 matrix materials, allowing electrons to quickly pass through the gaps between the TiNb2O7 matrix materials along the first conductive filler, preventing electron accumulation and loss at the point contact interfaces between the TiNb2O7 matrix materials. Based on this, the second conductive filler forms a network-like conductive framework that penetrates the carbon coating layer in the amorphous carbon binder phase, which is conducive to the formation of a high-speed electron transport conductive network.
[0025] Furthermore, in this application, the carbon-coated titanium niobium oxide is assembled from several primary particles. A first conductive filler provides linear local bridging between the primary particles, while a second conductive filler provides a network-like interconnection between them. This creates a three-tiered electronic conduction pathway within the secondary aggregates assembled from the primary particles, from the "TiNb2O7 matrix material surface (layer)" to the "linear local bridging" and then to the "network-like conductive framework penetrating the carbon coating layer." In other words, the amorphous carbon binder phase provides a tight interface with the TiNb2O7 matrix material surface, which is beneficial for improving the interfacial efficiency of charge transfer. The first conductive filler enhances the local electron transport performance between primary particles. The second conductive filler ensures long-range rapid electron transport at the macroscopic electrode scale.
[0026] In some embodiments, the first conductive filler is selected from at least one of single-walled carbon nanotubes and double-walled carbon nanotubes, and the second conductive filler is multi-walled carbon nanotubes; the amorphous carbon binder phase is obtained by carbonization of a carbon precursor, which is selected from water-soluble sugars, water-soluble organic acids, or water-soluble polymers. It should be understood that the water-soluble carbon precursor can be uniformly dissolved in the dispersion medium in a molecular state during wet milling and adsorbed onto the surface of the TiNb2O7 matrix material. After subsequent carbonization, it is transformed in situ into a continuous, uniform, and thickness-controllable amorphous carbon binder phase, ensuring that the surface of each TiNb2O7 matrix material is completely coated with a carbon layer, thereby forming an effective charge transfer interface layer. Based on this, single-walled and double-walled carbon nanotubes, possessing both small diameter and high flexibility, can extend from the carbon coating layer on the surface of the TiNb2O7 matrix material and bend across the nanoscale gaps between adjacent TiNb2O7 matrix materials, achieving localized bridging. Multi-walled carbon nanotubes have both large diameter and high rigidity, and are not easily bent or folded. Therefore, they can overlap with each other in amorphous carbon binder phase to form a stable three-dimensional through-conductive framework, providing long-distance transport channels for electrons.
[0027] It should be understood that the carbon precursor can be selected from at least one of glucose, sucrose, fructose, maltose, lactose, citric acid, ascorbic acid, tartaric acid, oxalic acid, polyvinylpyrrolidone, polyethylene glycol, and polyvinyl alcohol. More preferably, the carbon precursor is glucose, and the first conductive filler is a single-walled carbon nanotube.
[0028] In some embodiments, the ratio of the diameter of the TiNb2O7 matrix material to the thickness of the carbon coating layer on one side is (5~80):1. By selecting suitable raw materials, it is beneficial to obtain carbon-coated titanium niobium oxide with good electron transport properties, good stability in use, and long service life.
[0029] In some embodiments, the median particle size D50 of the TiNb2O7 matrix material is 0.08 μm to 0.15 μm. By selecting suitable raw materials, it is beneficial to obtain carbon-coated titanium niobium oxide with good electron transport properties, good stability in use, and long service life. It should be understood that the median particle size D50 of the TiNb2O7 matrix material can be 0.08 μm, 0.09 μm, 0.1 μm, 0.11 μm, 0.12 μm, 0.13 μm, 0.14 μm, or 0.15 μm.
[0030] In some embodiments, the thickness of one side of the carbon coating layer is 2nm to 5nm, and the thickness of one side of the carbon coating layer can be 2nm, 2.5nm, 3nm, 3.5nm, 4nm, 4.5nm, or 5nm.
[0031] In some embodiments, the mass ratio of TiNb2O7 matrix material, carbon precursor, first conductive filler, and second conductive filler is (80~120):(2~12):(0.1~0.6):(0.5~3). By selecting suitable raw materials, it is beneficial to obtain carbon-coated titanium niobium oxide with good electron transport performance, good stability in use, and long service life.
[0032] It should be understood that the preferred mass ratio of TiNb2O7 matrix material, carbon precursor, first conductive filler, and second conductive filler is 100:4:0.2:1.
[0033] On the other hand, the applicant found that when the amount of carbon precursor is too large, the resulting amorphous carbon binder phase is too thick, hindering ion transport. When the amount of the first conductive filler is too large, agglomeration is prone to occur, resulting in poor dispersibility. When the amount of the second conductive filler is too large, the formed conductive framework is too dense, making electrolyte wetting difficult.
[0034] In some embodiments, the mass of the TiNb2O7 matrix material is m1, and the sum of the masses of the carbon precursor, the first conductive filler, and the second conductive filler is m2, where 0.05m1≤m2≤0.16m1. By selecting suitable raw materials, it is beneficial to obtain carbon-coated titanium niobium oxide with good electron transport performance, good stability in use, and long service life.
[0035] In some embodiments, the median particle size D50 of the carbon-coated titanium niobium oxide is 0.5 μm to 5 μm. By selecting suitable raw materials, it is beneficial to obtain carbon-coated titanium niobium oxide with good electron transport properties, good stability in use, and long service life.
[0036] This application also provides a method for preparing carbon-coated titanium niobium oxide, comprising the following steps: S100, providing a titanium source and a niobium source, and calcining them to obtain a TiNb2O7 matrix material; S200, wet grinding the TiNb2O7 matrix material, a carbon precursor, and a conductive component to obtain a mixed slurry, and drying the mixed slurry to obtain an intermediate powder, wherein the conductive component includes a first conductive filler and a second conductive filler; S300, calcining the intermediate powder in a protective gas to coat the outer periphery of the TiNb2O7 matrix material with a carbon coating layer, wherein the carbon coating layer includes an amorphous carbon binder phase and a conductive component, the carbon precursor is converted into an amorphous carbon binder phase, at least a portion of the first conductive filler connects at least two TiNb2O7 matrix materials to form a conductive path, and at least a portion of the second conductive filler forms a conductive skeleton penetrating the carbon coating layer in the amorphous carbon binder phase, thereby obtaining carbon-coated titanium niobium oxide.
[0037] It should be understood that step S100, through calcination in air, and step S300, through calcination in a protective gas, can achieve carbon coating while maintaining the pure orthorhombic crystal structure of TiNb2O7, free of impurities. Furthermore, because orthorhombic TiNb2O7 possesses a unique Wadsley-Roth shear structure, it can provide three-dimensional lithium-ion diffusion channels. The presence of impurities such as TiO2 and Nb2O5 disrupts the continuity of these diffusion channels, thereby reducing capacity and rate performance. Therefore, this application maintains the pure-phase structure of TiNb2O7 after carbon coating, which is beneficial for improving the integrity of the lithium-ion diffusion channels.
[0038] Further, step S200 involves wet milling to obtain nanoscale particles, effectively shortening the lithium-ion solid-phase diffusion path and improving the ion transport rate. Based on this, spray drying is performed to obtain an intermediate powder, improving the material's flowability and processing performance, facilitating electrode coating. In other words, during wet milling, the carbon precursor, conductive component, and TiNb2O7 particles are thoroughly mixed and uniformly dispersed, and the mechanical force generated during milling promotes in-situ coating of the carbon precursor and conductive component on the TiNb2O7 surface. During spray drying, the carbon precursor and conductive component self-assemble on the TiNb2O7 surface to form a uniform coating layer. The secondary calcination process enables the carbon coating layer to form a tight chemical bond with the TiNb2O7 matrix material. Notably, the internal pores of the carbon-coated titanium niobium oxide provide channels for electrolyte penetration, increasing the contact area between the active material and the electrolyte.
[0039] In some embodiments, deionized water is used as the dispersion medium in wet milling, and drying in step S200 is achieved by spray drying. The inlet temperature of the spray dryer is 180°C to 250°C, and the outlet temperature is 80°C to 120°C. The protective gas is selected from at least one of argon, nitrogen, and helium.
[0040] On the other hand, deionized water is used as the dispersion medium in wet milling, avoiding the use and recycling of organic solvents during the preparation process. The method employs mature industrial equipment such as wet milling and spray drying, making it easy to scale up production. Furthermore, the raw materials are inexpensive and readily available. Compared to existing technologies using organic solvent systems or complex template methods, the preparation method provided in this application has greater advantages for industrialization.
[0041] In some embodiments, the titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, titanium isopropoxide, and titanium sulfate, and the niobium source is selected from at least one of niobium pentoxide, niobium pentachloride, niobium ethoxide, niobium oxalate, and ammonium niobium oxalate; the molar number of titanium in the titanium source is n1, the molar number of niobium in the niobium source is n2, and the ratio between n1 and n2 is (0.8~1.2):(1.5~2.5). By selecting appropriate types and amounts of raw materials, it is beneficial to obtain carbon-coated titanium niobium oxide with good electron transport performance, good stability in use, and long service life.
[0042] In some embodiments, in step S100, the calcination temperature is 800℃~1200℃, the calcination time is 2h~6h, and the calcination heating rate is 2℃ / min~5℃ / min; in step S300, the calcination temperature is 600℃~800℃, the calcination time is 2h~6h, and the calcination heating rate is 2℃ / min~5℃ / min. By selecting suitable preparation conditions, it is beneficial to obtain carbon-coated titanium niobium oxide with good electron transport performance, good stability in use, and long service life.
[0043] This application also provides an electrode sheet comprising carbon-coated titanium niobium oxide as described above or carbon-coated titanium niobium oxide prepared by the aforementioned preparation method. By selecting suitable preparation conditions, it is beneficial to obtain an electrode sheet with good electron transport performance, good stability in use, and long service life.
[0044] This application also provides a battery including at least one electrode as described above. By using the electrode provided in this application in the battery, the battery can maintain a stable discharge capacity of about 150 mAh / g at 69C (charging time of about 52 seconds) within a voltage range of 1.0V to 2.5V, and the battery retains ≥95% of its capacity after 100 cycles.
[0045] Example 1 Example 1 provides a method for preparing carbon-coated titanium niobium oxide and a battery, including the following steps: (1) Tetrabutyl titanate and niobium oxalate were weighed and added to deionized water for dispersion. The molar ratio of titanium in tetrabutyl titanate to niobium in niobium oxalate was 1:2. A first mixed slurry was prepared by wet grinding, and the median particle size D50 of the first mixed slurry was 0.5 μm. The first mixed slurry was spray-dried to obtain a first intermediate powder. The inlet temperature of the spray dryer was 220℃ and the outlet temperature was 100℃. The first intermediate powder was calcined at 1000℃ for 4 hours in air atmosphere to obtain TiNb2O7 matrix material.
[0046] (2) 100g of TiNb2O7 matrix material, 8g of glucose, 0.4g of single-walled carbon nanotubes (SWCNTs), and 2g of multi-walled carbon nanotubes (MWCNTs) were dispersed in deionized water and wet-milled to obtain a second mixed slurry. The median particle size D50 of the second mixed slurry was 0.10μm. The second mixed slurry was spray-dried to obtain a second intermediate powder. The inlet temperature of the spray dryer was 220℃ and the outlet temperature was 100℃.
[0047] (3) The second intermediate powder was heated to 700°C for 4 hours under an argon atmosphere at a heating rate of 3°C / min to obtain carbon-coated titanium niobium oxide.
[0048] (4) Carbon-coated titanium niobium oxide material, conductive carbon black (Super P) and polyvinylidene fluoride (PVDF) are mixed evenly in a mass ratio of 8:1:1 and coated onto a copper foil current collector. After drying and rolling, a negative electrode sheet is formed. The negative electrode sheet is used as the working electrode, a lithium metal sheet is used as the counter electrode, a 1 mol / L LiPF6 electrolyte (the solvent is ethylene carbonate (EC) and diethyl carbonate (DEC), with a volume ratio of EC to DEC of 1:1) is used as the electrolyte, and polypropylene (PP) is used as the separator. The CR2032 button cell is assembled in a glove box.
[0049] Example 2 The difference between Example 2 and Example 1 is that the amount of glucose used is 12g, the amount of SWCNT is 0.6g, and the amount of MWCNT is 3g.
[0050] Example 3 The difference between Example 3 and Example 1 is that the amount of glucose used is 4g, the amount of SWCNT is 0.2g, and the amount of MWCNT is 1g.
[0051] Example 4 The difference between Example 4 and Example 1 is that the median particle size D50 in the second mixed slurry is 0.09 μm, the calcination temperature in step (3) is 750℃, the heating rate is 4℃ / min, and the calcination time is 3h.
[0052] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that SWCNT and MWCNT were not added.
[0053] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that step (2) was not performed.
[0054] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the amount of SWCNT used is 2g and the amount of MWCNT used is 1g.
[0055] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that the amount of MWCNT used is 4g.
[0056] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that steps (1) to (3) are replaced by: weighing titanium dioxide and niobium pentoxide, with the molar ratio of titanium in titanium dioxide to niobium in niobium pentoxide being 1:2. After ball milling and mixing, the mixture is calcined at 1100°C in air for 12 hours to obtain the electrode material, which has a particle size of about 2 to 5 μm.
[0057] Comparative Example 6 The difference between Comparative Example 6 and Example 1 is that the amount of glucose used is 10g.
[0058] Comparative Example 7 The difference between Comparative Example 7 and Example 1 is that the median particle size D50 in the second mixed slurry is 0.06 μm.
[0059] Comparative Example 8 The difference between Comparative Example 8 and Example 1 is that the median particle size D50 in the second mixed slurry is 0.18 μm.
[0060] Comparative Example 9 The difference between Comparative Example 9 and Example 1 is that the calcination temperature in step (3) is 550°C.
[0061] Comparative Example 10 The difference between Comparative Example 10 and Example 1 is that the calcination temperature in step (3) is 850°C.
[0062] Comparative Example 11 The difference between Comparative Example 11 and Example 1 is that SWCNT was not added.
[0063] Comparative Example 12 The difference between Comparative Example 12 and Example 1 is that MWCNT was not added.
[0064] Performance testing The lithium-ion batteries prepared in Examples 1-4 and Comparative Examples 1-12 were subjected to electrochemical performance tests in the voltage range of 1.0V to 2.5V. The specific test conditions were as follows: (1) Constant current discharge was performed at a rate of 0.1C, and the first discharge capacity was recorded; (2) Constant current discharge was performed at a rate of 69C, and the discharge capacity at this rate was recorded; (3) Constant current charge-discharge cycle test was performed in the voltage range of 1.0V to 2.5V, with 100 cycles. The discharge capacity of the first and 100th cycles was recorded, and the capacity retention rate was calculated.
[0065] Table 1: Performance Tests of Lithium-ion Batteries
[0066] Table 2: Comparison of key process parameters and performance of Comparative Examples 1-6
[0067] Depend on Figure 1 It can be seen that the carbon-coated titanium niobium oxide material prepared in Example 1 has a uniform microsphere morphology with a diameter of approximately 0.5 μm to 5 μm, assembled from nanoscale primary particles. Based on the test results in Tables 1 and 2, compared with Example 1, Comparative Example 7, and Comparative Example 8, there is an optimal range for the grinding particle size (0.08 μm to 0.15 μm). When the particle size is too fine (<0.08 μm), the surface energy of the nanoparticles is too high, leading to easy agglomeration and decreased carbon coating uniformity; when the particle size is too coarse (>0.15 μm), the lithium-ion diffusion path is prolonged, resulting in insufficient ultra-high rate kinetics. Only by controlling D50 within the range of 0.08 to 0.15 μm can optimal ultra-fast charging performance be obtained. Comparing Example 1, Comparative Example 9, and Comparative Example 10, there is also an optimal calcination temperature window (600℃ to 800℃). At excessively low temperatures (<600℃), the carbon source carbonization is insufficient, resulting in poor conductivity and weak bonding between the carbon layer and the matrix. At excessively high temperatures (>800℃), TiNb2O7 undergoes a phase transformation to generate impurity phases (TiO2), disrupting the integrity of the Wadsley-Roth shear structure. Only by controlling the secondary calcination temperature between 600℃ and 800℃ can a high-quality carbon coating layer be obtained while maintaining a pure-phase orthorhombic crystal structure. Comparing Examples 1, 3, 4, and 6, it is evident that the three carbon source ratios exhibit a narrow "synergistic window." Excessive SWCNT leads to agglomeration, excessive MWCNT leads to impregnation difficulties, and excessive glucose leads to an excessively thick carbon layer. All three disrupt the synergistic effect of the multi-level conductive network of "layer-wire-network," resulting in a significant decrease in 69C capacity. Example 4, by simultaneously optimizing the grinding particle size (0.09 μm) and calcination temperature (750 °C), further improved the 69C capacity to 153 mAh / g and the cycle retention rate to 97.0% compared to Example 1. This indicates that there is a synergistic enhancement effect among the process parameters of the present invention, and the best overall electrochemical performance can be obtained when all parameters are within their preferred ranges. Comparison with Example 1 and Comparative Examples 11-12 shows that the simultaneous addition of SWCNTs and MWCNTs is beneficial for constructing a complete conductive network, and the absence of either conductive filler will reduce electron transport performance.
[0068] like Figure 2 As shown, X-ray diffraction (XRD) characterization of the carbon-coated titanium niobium oxide material prepared in Example 1 showed that TiNb2O7 in Example 1 has a pure phase orthorhombic crystal structure with no impurity phase peaks.
[0069] XRD characterization of the carbon-coated titanium niobium oxide material prepared in Comparative Example 10 showed trace TiO2 impurity phase peaks (rutile phase, 2θ≈27.4°), indicating that some TiNb2O7 decomposed or underwent phase transformation at excessively high temperatures.
[0070] In summary, the carbon layer conductive network formed by coating with a single carbon source is discontinuous, has high interfacial impedance, and offers limited improvement to ultra-fast charging performance. Excessive amounts of conductive components tend to agglomerate, resulting in poor dispersibility and weak bonding with the TiNb2O7 matrix, making it difficult to construct stable three-dimensional conductive pathways and affecting long-term cycling stability.
[0071] The basic principles, main features, and advantages of this application have been described above. Those skilled in the art should understand that this application is not limited to the above embodiments. The embodiments and descriptions in the specification are merely the principles of this application. Various changes and modifications can be made to this application without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claims. The scope of protection claimed by this application is defined by the appended claims and their equivalents.
Claims
1. A carbon-coated titanium-niobium oxide, characterized in that, The carbon-coated titanium niobium oxide is assembled from several primary particles, which include: TiNb2O7 matrix material; A carbon coating layer is applied to the outer periphery of the TiNb2O7 matrix material. The carbon coating layer includes an amorphous carbon binder phase and a conductive component. At least a portion of the amorphous carbon binder phase connects the TiNb2O7 matrix material and the conductive component. The conductive component is dispersed in the amorphous carbon binder phase. The conductive component includes a first conductive filler and a second conductive filler. At least a portion of the first conductive filler connects to the TiNb2O7 matrix material in at least two of the primary particles to form a conductive path. At least a portion of the second conductive filler forms a conductive framework that penetrates the carbon coating layer in the amorphous carbon binder phase of the plurality of primary particles.
2. The carbon-coated titanium niobium oxide according to claim 1, characterized in that, The first conductive filler is selected from at least one of single-walled carbon nanotubes and double-walled carbon nanotubes, and the second conductive filler is multi-walled carbon nanotubes. The amorphous carbon binder phase is obtained by carbonization of a carbon precursor, which is selected from water-soluble sugars, water-soluble organic acids, or water-soluble polymers.
3. The carbon-coated titanium niobium oxide according to claim 2, characterized in that, At least one of the following conditions must be met: (a) The ratio of the diameter of the TiNb2O7 matrix material to the thickness of one side of the carbon coating layer is (5~80):1; (b) The median particle size D50 of the TiNb2O7 matrix material is 0.08 μm to 0.15 μm; (c) The mass ratio of the TiNb2O7 matrix material, the carbon precursor, the first conductive filler, and the second conductive filler is (80~120):(2~12):(0.1~0.6):(0.5~3); (d) The mass of the TiNb2O7 matrix material is m1, and the total mass of the carbon precursor, the first conductive filler, and the second conductive filler is m2, where 0.05m1≤m2≤0.16m1; (e) The median particle size D50 of the carbon-coated titanium niobium oxide is 0.5 μm to 5 μm.
4. A method for preparing carbon-coated titanium niobium oxide, characterized in that, Including the following steps: S100 provides titanium and niobium sources, which are then calcined to obtain TiNb2O7 matrix material; S200: The TiNb2O7 matrix material, carbon precursor and conductive component are wet-milled to obtain a mixed slurry, and the mixed slurry is dried to obtain an intermediate powder. The conductive component includes a first conductive filler and a second conductive filler. S300. The intermediate powder is calcined in a protective gas to coat the outer periphery of the TiNb2O7 matrix material with a carbon coating layer. The carbon coating layer includes an amorphous carbon binder phase and the conductive component. The carbon precursor is converted into the amorphous carbon binder phase. At least a portion of the first conductive filler connects at least two of the TiNb2O7 matrix materials to form a conductive path. At least a portion of the second conductive filler forms a conductive framework penetrating the carbon coating layer in the amorphous carbon binder phase, thereby obtaining carbon-coated titanium niobium oxide.
5. The preparation method according to claim 4, characterized in that, The titanium source is selected from at least one of titanium dioxide, tetrabutyl titanate, titanium isopropoxide, and titanium sulfate; the niobium source is selected from at least one of niobium pentoxide, niobium pentachloride, niobium ethanol, niobium oxalate, and ammonium niobium oxalate; the number of moles of titanium in the titanium source is n1, the number of moles of niobium in the niobium source is n2, and the ratio between n1 and n2 is (0.8~1.2):(1.5~2.5).
6. The preparation method according to claim 4, characterized in that, The mass ratio of the TiNb2O7 matrix material, the carbon precursor, the first conductive filler, and the second conductive filler is (80~120):(2~12):(0.1~0.6):(0.5~3).
7. The preparation method according to claim 4, characterized in that, In step S100, the calcination temperature is 800℃~1200℃, the calcination time is 2h~6h, and the calcination heating rate is 2℃ / min~5℃ / min. In step S300, the calcination temperature is 600℃~800℃, the calcination time is 2h~6h, and the calcination heating rate is 2℃ / min~5℃ / min.
8. The preparation method according to any one of claims 4 to 7, characterized in that, The median particle size D50 of the TiNb2O7 matrix material is 0.08μm to 0.15μm, the single-sided thickness of the carbon coating layer is 2nm to 5nm, and the median particle size D50 of the carbon-coated titanium niobium oxide is 0.5μm to 5μm.
9. An electrode sheet, characterized in that, This includes carbon-coated titanium niobium oxide as described in any one of claims 1 to 3, or carbon-coated titanium niobium oxide prepared by the preparation method described in any one of claims 4 to 8.
10. A battery, characterized in that, It includes at least one electrode as described in claim 9.
